Faktor Non Financial Dan Islamic Social Reporting Disclosure Perbankan Syariah Indonesia - Eka Widiastuti; Muhammad Asmeldi Firman (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2016)
The study aims to investigate the Islamic Social Reporting Disclosure (ISRD) practicesin Sharia Banks of Indonesia and determine the non financial factors that may influence to level of ISRD on 2010 – 2012. The samples in this study are 30 annual reports of sharia banks for three years. Level of ISRD is measured by ISR index that have six categories including investment and finance, corporate governance, product and services, employee, society, and environment. This study identified three non financial factors that influence to level of ISRD such as Media Exposure, main institusional ownership, and Islamic governance score (IG-score). Average ISR disclosure for three years had reached 55%. The test result by multiple linear regression test showed that only Media Exposure and IG-score have a significant to level of ISRD positively. On the other side, main institusional ownership doesn’t have a significant to level of ISRD. In addition, this study found profitability as control variable doesn’t have a significant to level ISRD too.